Modernization of electrical complex for producing thermal energy for an industrial enterprise - Chebotarova, Yevheniia; Perekrest, Andrii (Technology audit and production reserves, 2021)
The object of research is the electrical complex for the preparation of thermal energy at the enterprise. The electrotechnical complex is a heat supply unit that provides thermal energy to the building of the enterprise for the needs of heating, ventilation and hot water supply. One of the identified shortcomings of this facility is the overconsumption of energy resources for heating, caused by the lack of the ability to control consumption. Modernization of heat points and equipping them with automation means will provide quantitative and qualitative control of the heat carrier depending on the outside air temperature. In the course of the study, the method of statistical data analysis was used to analyze the heat load of buildings for heating, ventilation and hot water supply, and the distribution of heat loads by the temperature of the indoor air. Also, an improved discounted method for evaluating the effectiveness of investment projects was used when calculating economic indicators and a method for calculating heat consumption for heating according to aggregated indicators when determining energy consumption for heating. On the basis of the analysis of the heat load and a certain structure of its distribution according to the temperature of the internal air, it was found that more energy resources are consumed for heating. The largest consumer is defined as a building with an internal temperature Tin=16 °C. Calculations of the commercial attractiveness of the proposed technical solutions for buildings with an internal temperature Tin=18 °C have confirmed the feasibility of their implementation in terms of their payback, which does not exceed the period of 3.5 heated seasons. Thanks to the modernization of heat points and the introduction of automated monitoring and regulation systems, optimal heat energy consumption will be ensured depending on the ambient temperature. Unlike other similar studies, the feasibility of introducing automated systems is determined by an improved discounted method, which allows not only to take into account the change in the value of money in the future, but also the required minimum percentage of thermal energy savings to break even projects.